Immunobiological Characteristics of the Attenuated African Swine Fever Virus Strain Katanga-350 - Alexey D. Sereda; Mikhail E. Vlasov; Galina S. Koltsova; Sergey Y. Morgunov; Dmitry A. Kudrjashov; Irina P. Sindryakova; Olga L. Kolbasova; Valentina M. Lyska; Andrei Y. Koltsov; Sergey P. Zhivoderov; Elena Y. Pivova; Vladimir M. Baluishev; et al. (Viruses, 2022)
The African swine fever virus (ASFV) is the cause of a recent pandemic that is threatening the global pig industry. The virus infects domestic and wild pigs and manifests with a variety of clinical symptoms, depending on the strain. No commercial vaccine is currently available to protect animals from this virus, but some attenuated and recombinant live vaccine candidates might be effective against the disease. This article describes the immunobiological characteristics of one such candidate—the laboratory-attenuated ASFV strain, Katanga-350—which belongs to genotype I. In this study, we assessed clinical signs and post-mortem changes, the levels of viremia and the presence of viral DNA caused by injection of ASF virus strains Katanga-350, Lisbon-57, and Stavropol 08/01. Intramuscular injection of this strain protected 80% of pigs from a virulent strain of the same genotype and seroimmunotype (Lisbon-57). At least 50% of the surviving pigs received protection from subsequent intramuscular infection with a heterologous (genotype II, seroimmunotype VIII) virulent strain (Stavropol 08/01). Virus-specific antibodies were detectable in serum and saliva samples between 8–78 days after the first inoculation of the Katanga-350 strain (the observational period). The results suggested that this strain could serve as a basis for the development of a recombinant vaccine against ASF viruses belonging to seroimmunotype I.